Application of holistic medicine in the field of reproductive medicine: is it right to only focus on cells and organs? It is a time to convert to a new paradigm in reproductive medicine. Issue 3 (September 2018) - Morimoto, Yoshiharu; Ida, Mamoru; Inoue, Tomoko; Fukuda, Aisaku
Abstract : About 40 years progress of artificial reproductive technology made dream of many patients come true. However, there still remain many patients with recurrent failures of IVF by the conventional technologies. It is because we have too much focused on cells such as oocyte and sperm, and organs such as uterus, ovary, and testis. It is a time to convert to new paradigm in reproductive medicine. We should treat the whole body that includes mind and whole body. Integrated medicine considering nutrition, mental care, and other alternative medicine should be applied to raise success in artificial reproductive technology. If we can collect high quality evidence from the field, it would open the window for new era and solve issues that cannot be treated via conventional western technologies.